“So Were I Equalled in Renown:” Autobiographical Elements and the Epic Poet's Career in Milton - Maria Rita Drumond Viana; Andrey Felipe Martins (Ilha do Desterro)
John Milton is outlier among poets of the seventeenth century in his extensive recourse to details of his personal life, which are made integral part, covertly or explicitly, of his many works. From the early “Nativity Ode” onwards we can identify confessional passages in many of his poems that can be read autobiographically. What draws our attention to Milton’s case is that it also prefigures a major cultural and political revolution, in which the legitimacy of the individual consciousness was revalued. The main aim of this article is to explore specific moments in Milton’s oeuvre in which the autobiographical vein comes into sharp focus. Differently from his more mature work, in which he does not waver in confidence, in the earlier writings we can spot the doubts and anxieties of an apprentice poet of unbounded aspiration.